Radiological characterisation and inter-laboratory comparison of naturally occurring radioactive materials (NORM) in building materials used in Ireland - R.E. Djabou; M. Dodek; C. Sainz; I. Fuente; L. León Vintró; O. Hanley; J. Goggins; M. Foley (Science of The Total Environment, 2026)

Advancing nonclinical blood pressure assessment: Current practices and future directions in drug development - Michael K. Pugsley; Siddhartha Bhatt; Christer Gottfridsson; Peter Hoffmann; Yevgeniya E. Koshman; Kevin Norton; Claire E. O'Brien; Jennifer Pierson; Eric I. Rossman; Alexandra Taraboletti; Tanja S. Zabka; C. Michael Foley (Regulatory Toxicology and Pharmacology, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

Boater Compliance with Speed Regulations in High-Risk Areas for Marine Turtle Watercraft Strikes - Mariana M. P. B. Fuentes; Jessica Z. D’Auria; Stephanie Viegas Gkionis; Camille Kynoch; Joshua C. Manning; Sophie Mills; Sophie Rosengarten; Julia Saltzman; Armando Barsante Santos; Allen M. Foley (Coastal Management, 2026)

Gamma emissions from NORM in building materials: A position paper on national transposition of the Euratom basic safety standard - M. Dodek; R.E. Djabou; C. Sainz; I. Fuente; L.L. Vintró; O. Hanley; J. Goggins; M. Foley (Journal of Environmental Radioactivity, 2026)

Benign cardiac troponin I release induced by elevated beat rate is associated with membrane bleb formation - Jomana Hatahet; Hannah J. Nonarath; Mark T. Zafiratos; Geena Jasiek; Rebecca Kohnken; Jessica Treadway; C. Michael Foley (Toxicology and Applied Pharmacology, 2026)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Protein vicinal thiols as intrinsic probes of brain redox states in health, aging, and ischemia - Timothy D. Foley; Wen C. Huang; Emily A. Petsche; Emily R. Fleming; James C. Hornickle (Metabolic Brain Disease, 2024)
The nature of brain redox metabolism in health, aging, and disease remains to be fully established. Reversible oxidations, to disulfide bonds, of closely spaced (vicinal) protein thiols underlie the catalytic maintenance of redox homeostasis by redoxin enzymes, including thioredoxin peroxidases (peroxiredoxins), and have been implicated in redox buffering and regulation. We propose that non-peroxidase proteins containing vicinal thiols that are responsive to physiological redox perturbations may serve as intrinsic probes of brain redox metabolism. Using redox phenylarsine oxide (PAO)-affinity chromatography, we report that PAO-binding vicinal thiols on creatine kinase B and alpha-enolase from healthy rat brains were preferentially oxidized compared to other selected proteins, including neuron-specific (gamma) enolase, under conditions designed to trap in vivo protein thiol redox states. Moreover, measures of the extents of oxidations of vicinal thiols on total protein, and on creatine kinase B and alpha-enolase, showed that vicinal thiol-linked redox states were stable over the lifespan of rats and revealed a transient reductive shift in these redox couples following decapitation-induced global ischemia. Finally, formation of disulfide-linked complexes between peroxiredoxin-2 and brain proteins was demonstrated on redox blots, supporting a link between protein vicinal thiol redox states and the peroxidase activities of peroxiredoxins. The implications of these findings with respect to underappreciated aspects of brain redox metabolism in health, aging, and ischemia are discussed.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Taking flight: An ecological, evolutionary and genomic perspective on bat telomeres - Megan L. Power; Nicole M. Foley; Gareth Jones; Emma C. Teeling (Molecular Ecology, 2022)
Over 20% of all living mammals are bats (order Chiroptera). Bats possess extraordinary adaptations including powered flight, laryngeal echolocation and a unique immune system that enables them to tolerate a diversity of viral infections without presenting clinical disease symptoms. They occupy multiple trophic niches and environments globally. Significant physiological and ecological diversity occurs across the order. Bats also exhibit extreme longevity given their body size with many species showing few signs of ageing. The molecular basis of this extended longevity has recently attracted attention. Telomere maintenance potentially underpins bats’ extended healthspan, although functional studies are still required to validate the causative mechanisms. In this review, we detail the current knowledge on bat telomeres, telomerase expression, and how these relate to ecology, longevity and life‐history strategies. Patterns of telomere shortening and telomerase expression vary across species, and comparative genomic analyses suggest that alternative telomere maintenance mechanisms evolved in the longest‐lived bats. We discuss the unique challenges faced when working with populations of wild bats and highlight ways to advance the field including expanding long‐term monitoring across species that display contrasting life‐histories and occupy different environmental niches. We further review how new high quality, chromosome‐level genome assemblies can enable us to uncover the molecular mechanisms governing telomere dynamics and how phylogenomic analyses can reveal the adaptive significance of telomere maintenance and variation in bats.

Middle Jurassic–Lower Cretaceous stratigraphy of the northern Great Australian Superbasin: insights from maximum depositional age constraints from the U–Pb detrital zircon record - E. K. Foley; E. M. Roberts; R. A. Henderson; C. N. Todd; E. M. Knutsen; C. Spandler (Australian Journal of Earth Sciences, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster - Pamela C. Lovejoy; Kate E. Foley; Melissa M. Conti; Samantha M. Meadows; Christopher Bishop; Anthony C. Fiumera (Molecular Ecology, 2021)
Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster , and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.

Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis - Nicole M. Foley; Eric J. Petit; Thomas Brazier; John A. Finarelli; Graham M. Hughes; Frédéric Touzalin; Sébastien J. Puechmaille; Emma C. Teeling (Molecular Ecology, 2020)
Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2 = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats.

Correcting for within-season demographic turnover to estimate the island-wide population of King Penguins (Aptenodytes patagonicus) on South Georgia - C. M. Foley; W. F. Fagan; H. J. Lynch (Polar Biology, 2020)

Chronic Dyrk1 Inhibition Delays the Onset of AD-Like Pathology in 3xTg-AD Mice - R. Velazquez; B. Meechoovet; A. Ow; C. Foley; A. Shaw; B. Smith; S. Oddo; C. Hulme; Travis Dunckley (Molecular Neurobiology, 2019)

Microbial assemblages reflect environmental heterogeneity in alpine streams - Scott Hotaling; Mary E. Foley; Lydia H. Zeglin; Debra S. Finn; Lusha M. Tronstad; J. Joseph Giersch; Clint C. Muhlfeld; David W. Weisrock (Global Change Biology, 2019)
Alpine streams are dynamic habitats harboring substantial biodiversity across small spatial extents. The diversity of alpine stream biota is largely reflective of environmental heterogeneity stemming from varying hydrological sources. Globally, alpine stream diversity is under threat as meltwater sources recede and stream conditions become increasingly homogeneous. Much attention has been devoted to macroinvertebrate diversity in alpine headwaters, yet to fully understand the breadth of climate change threats, a more thorough accounting of microbial diversity is needed. We characterized microbial diversity (specifically Bacteria and Archaea) of 13 streams in two disjunct Rocky Mountain subranges through 16S rRNA gene sequencing. Our study encompassed the spectrum of alpine stream sources (glaciers, snowfields, subterranean ice, and groundwater) and three microhabitats (ice, biofilms, and streamwater). We observed no difference in regional (γ) diversity between subranges but substantial differences in diversity among (β) stream types and microhabitats. Within‐stream (α) diversity was highest in groundwater‐fed springs, lowest in glacier‐fed streams, and positively correlated with water temperature for both streamwater and biofilm assemblages. We identified an underappreciated alpine stream type—the icy seep—that are fed by subterranean ice, exhibit cold temperatures (summer mean

Evaluation of Demodex mite viability using motility and scattered light intensity - S. Gatault; R. Foley; L. Shiels; F. C. Powell (Experimental and Applied Acarology, 2019)

King Penguin populations increase on South Georgia but explanations remain elusive - C. M. Foley; T. Hart; H. J. Lynch (Polar Biology, 2018)

Effects of DHA on Hippocampal Autophagy and Lysosome Function After Traumatic Brain Injury - Yan Yin; Eric Li; George Sun; Hong Q. Yan; Lesley M. Foley; Liwia A. Andrzejczuk; Insiya Y. Attarwala; T. Kevin Hitchens; Kirill Kiselyov; C. Edward Dixon; Dandan Sun (Molecular Neurobiology, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Sexual Health Concerns Among Cancer Survivors: Testing a Novel Information-Need Measure Among Breast and Prostate Cancer Patients - Sheila A. Crowley; Sallie M. Foley; Daniela Wittmann; Christina H. Jagielski; Rodney L. Dunn; Patricia M. Clark; Jennifer J. Griggs; Catherine Peterson; Marcia Leonard; Lawrence C. An; John T. Wei; James E. Montie; et al. (Journal of Cancer Education, 2016)

Mitigation of Acid Mine Drainage via a Revegetation Programme in a Closed Coal Mine in Southern New Zealand - C. G. Rufaut; D. Craw; Andrea Foley (Mine Water and the Environment, 2015)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Auxin and ABA act as central regulators of developmental networks associated with paradormancy in Canada thistle (Cirsium arvense) - James V. Anderson; Münevver Doğramacı; David P. Horvath; Michael E. Foley; Wun S. Chao; Jeffrey C. Suttle; Jyothi Thimmapuram; Alvaro G. Hernandez; Shahjahan Ali; Mark A. Mikel (Functional & Integrative Genomics, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Trace element variations in olivine phenocrysts from Ugandan potassic rocks as clues to the chemical characteristics of parental magmas - Stephen F. Foley; Dorrit E. Jacob; Hugh St. C. O’Neill (Contributions to Mineralogy and Petrology, 2011)

Observations of a western North Atlantic right whale ( Eubalaena glacialis ) birth offshore of the protected southeast U.S. critical habitat - H. J. Foley; R. C. Holt; R. E. Hardee; P. B. Nilsson; K. A. Jackson; A. J. Read; D. A. Pabst; W. A. McLellan (Marine Mammal Science, 2011)

A comparative study of methanol as a supplementary carbon source for enhancing denitrification in primary and secondary anoxic zones - Maneesha P. Ginige; Jocelyn C. Bowyer; Leah Foley; Jürg Keller; Zhiguo Yuan (Biodegradation, 2009)

Co-phylogenetic analysis of Anaplasma phagocytophilum and its vectors, Ixodes spp. ticks - Janet Foley; Nathan C. Nieto; Patrick Foley; Mike B. Teglas (Experimental and Applied Acarology, 2008)

Methyl jasmonate does not induce changes in Eucalyptus grandis leaves that alter the effect of constitutive defences on larvae of a specialist herbivore - M. L. Henery; I. R. Wallis; C. Stone; W. J. Foley (Oecologia, 2008)

Effects of poaching on bull mating success in a free ranging African elephant (Loxodonta africana) population in Tarangire National Park, Tanzania - D. R. S. Ishengoma; A. M. Shedlock; C. A. H. Foley; L. J. Foley; S. K. Wasser; S. T. Balthazary; B. M. Mutayoba (Conservation Genetics, 2008)

MRI evaluation of topical heat and static stretching as therapeutic modalities for the treatment of eccentric exercise-induced muscle damage - R. C. Jayaraman; R. W. Reid; J. M. Foley; B. M. Prior; G. A. Dudley; K. W. Weingand; R. A. Meyer (European Journal of Applied Physiology, 2004)

Evaluating the influence of different vegetation biomes on the global climate - P. K. Snyder; C. Delire; J. A. Foley (Climate Dynamics, 2004)

A model of carbon evasion and sedimentation in temperate lakes - Paul C. Hanson; Amina I. Pollard; Darren L. Bade; Katie Predick; Stephen R. Carpenter; Jonathan A. Foley (Global Change Biology, 2004)
Lakes process terrigenous carbon. The carbon load processed by lakes may partially offset estimates made for terrestrial net ecosystem exchange ( NEE ). The balance within lakes between carbon burial and evasion to the atmosphere determines whether lakes are net sinks or net sources of atmospheric carbon. Here we develop a model to study processing of both autochthonous and allochthonous carbon sources in lakes. We run the model over gradients of dissolved organic carbon ( DOC ) and total phosphorus ( TP ) concentrations found in the Northern Highlands Lake District of Wisconsin. In our model, lakes processed between 5 and 28 g C m −2 (watershed) yr −1 derived from the watershed, which approximates one‐tenth of NEE for similar terrestrial systems without lakes. Most lakes were net heterotrophic and had carbon evasion in excess of carbon burial, making them net sources of carbon to the atmosphere. Only lakes low in DOC and moderate to high in TP were net autotrophic and net sinks of carbon from the atmosphere.

Comparison of the climate simulated by the CCM3 coupled to two different land-surface models - Delire C.; Levis S.; Bonan G.; Foley J.; Coe M.; Vavrus S. (Climate Dynamics, 2002)

Noninvasive Stress and Reproductive Measures of Social and Ecological Pressures in Free‐Ranging African Elephants - C. A. H. Foley; S. Papageorge; S. K. Wasser (Conservation Biology, 2001)
The African elephant ( Loxodonta africana ) experienced a poaching‐related 60% population decline between 1979 and 1988 that was inordinately concentrated on adults. This, coupled with political pressures to delist the elephant, has created a need for noninvasive physiological measures that can quantify the long‐term effects of past mortality patterns of this long‐lived species. We collected fresh fecal samples from 16 female elephants in three different groups over 23 months at Tarangire National Park, Tanzania, and analyzed them for fecal progesterone and cortisol metabolites. Social and ecological measures were collected concurrently. Fecal progesterone metabolite measures corresponded significantly with stage of gestation, and appear to be able to confirm pregnancy in female elephants from as early as 3 months of gestation. We found that progesterone metabolite concentrations were significantly lower during the dry season than during the wet season after controlling for stage of gestation. Fecal cortisol metabolite concentrations showed the opposite seasonal pattern, being significantly higher in the dry season and inversely correlated with rainfall across seasons. Fecal cortisol metabolite concentrations also increased with group size and were correlated positively with dominance rank in the largest group. Our results suggest that measures of progesterone and cortisol metabolites in feces provide indices of reproductive function and physiological stress that can quantify both natural and human disturbances in African elephants. These measures are ideally suited for monitoring the long‐term effects of social disruption from poaching and a variety of other management concerns.

Biarticular and monoarticular muscle activation and injury in human quadriceps muscle - Barry M. Prior; Roop C. Jayaraman; Robert W. Reid; Thomas G. Cooper; Jeanne M. Foley; Gary A. Dudley; Ronald A. Meyer (European Journal of Applied Physiology, 2001)

Analysis of type 1 metallothionein cDNAs in Vicia faba - Rhonda C. Foley; Zhi Mei Liang; Karam B. Singh (Plant Molecular Biology, 1997)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Chemical and biological studies on 1,2-dihydro-s-triazines - G. E. Foley; E. J. Modest; S. Farber; E. C. Haley (Antonie van Leeuwenhoek, 1955)

Chemical and biological studies on 1,2-dihydro-S-triazines - G. E. Foley; E. C. Haley (Antonie van Leeuwenhoek, 1955)

Chemical and biological studies on 1,2-dihydro-s-triazines - G. E. Foley; E. C. Haley (Antonie van Leeuwenhoek, 1955)

Chemical and biological studies on 1,2-dihydro-s-triazines - G. E. Foley; E. C. Haley (Antonie van Leeuwenhoek, 1955)